2007
DOI: 10.1007/s10620-006-9630-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of Specific Antibodies to an ARF Protein in Treated Patients with Chronic HCV Infection

Abstract: The hepatitis C virus (HCV) F protein is a recently described, frameshift product of HCV core encoding sequence with unknown biological function. In this study we sought to characterize the prevalence of specific anti-F antibodies in patients with chronic HCV infection and to analyze the anti-F antibody profile before, during, and after antiviral treatment in order to gain a better understanding of the role of F protein in HCV pathogenesis. Serum samples were collected from 44 patients with chronic HCV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 21 publications
7
29
1
7
Order By: Relevance
“…Furthermore, to investigate the lack of cross reactivity between core and F some samples were tested for both Core and F antibody in which there were some samples reacting with Core without any significant detection of F antibody (data not shown). The seroprevalence of anti-F antibodies in our study is in accordance with the results reported by Cohen et al who investigated specific anti-F antibodies in 89% of the 1b hepatitis C patients in Israel (18), but are higher than those reported by Miladi et al who observed anti-F antibodies only in an estimated 10% of HCV patients infected with genotype 1b in France (17). To our knowledge there is only one report of 62% seroprevalance of anti F in 1a chronically infected patients in France (20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, to investigate the lack of cross reactivity between core and F some samples were tested for both Core and F antibody in which there were some samples reacting with Core without any significant detection of F antibody (data not shown). The seroprevalence of anti-F antibodies in our study is in accordance with the results reported by Cohen et al who investigated specific anti-F antibodies in 89% of the 1b hepatitis C patients in Israel (18), but are higher than those reported by Miladi et al who observed anti-F antibodies only in an estimated 10% of HCV patients infected with genotype 1b in France (17). To our knowledge there is only one report of 62% seroprevalance of anti F in 1a chronically infected patients in France (20).…”
Section: Discussionsupporting
confidence: 92%
“…Among the HCV proteins, NS5A, E2, and NS3 have been shown to interfere with IFN-α or -β treatment, causing antiviral resistance (16,24). The HCV core protein perturbs the function of cellular proteins involved in T-cell proliferation and induces apoptosis, thereby leading to immune suppression and liver damage (18). Our results confirm the expression of F protein during natural HCV infection, but the role of F protein in the HCV life cycle and the significance of anti-F antibodies in chronic HCV infection have yet to be elucidated.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…HCV is one of the leading causes of persistent infection in humans that can predispose to liver fibrosis and cirrhosis. There are some reports indicating that chronic hepatitis C (CHC) infection is strongly associated with hepatocellular carcinoma (HCC) (3)(4)(5)(6)(7)(8)(9). There is neither effective vaccine for immunization, nor a broadly effective treatment for HCV infection (3).Among different factors associated with chronic HCV infection, alternate reading frame protein (ARFP) or core+1 protein is one the newest ones that can promote persistent infection (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that core+1 protein interacts with p21, leading to inhibition of the cell cycle (16). Cohen et al, (5) suggested no significant correlation between the presence of anti-core+1 antibody (Ab) and HCV viremia or antiviral therapy outcome, while Gao et al, (17) found a correlation between anti-core+1 Ab and the outcome of treatment in patients infected with HCV. Many studies suggested the critical role of core+1 protein in humoral response, HCV infection status (12,18) as well as outcomes (11, Copyright © 2018, Jundishapur Journal of Microbiology.…”
Section: Introductionmentioning
confidence: 99%